Analysis of Velocity, Power and Skin Temperature in Paralympic Powerlifting Athletes with Fixed and Variable Resistance - Gildo Francisco dos Santos Filho; Felipe J. Aidar; Márcio Getirana-Mota; Ciro José Brito; Esteban Aedo-Muñoz; Ângelo de Almeida Paz; Joilson Alves de Souza Leite Júnior; Edson Lucas Monteiro Vieira; Pantelis T. Nikolaidis (MDPI AG, 2024)
Variable resistance training has been widely used in athletic preparation. Objectives: To analyze the use of currents (VRT) and the traditional method (TRAD) on speed, power and temperature in a training session. Methods: Fourteen paralympic powerlifting (PP) athletes took part over three weeks. In week 1, familiarization and 1RM tests took place, and, in weeks 2 and 3, pre- and post-training took place, where the propulsive mean velocity and power and temperatures were assessed before and after, at 24 h and 48 h. Results: There was a difference in the sternal pectoral temperatures before and after VRT (p = 0.040) and at 48 h for TRAD and VRT (p = 0.018); in the clavicular pectoralis before and after VRT and TRAD (p = 0.003); in the anterior deltoid after and at 48 h for TRAD and VRT (p = 0.026 and p = 0.017); and in the triceps after and at 24 h and 48 h between TRAD and VRT (p = 0.005). In the training series, the MPV was significant in TRAD between Set1 and Set5 (p = 0.003), in training (VRT) between Set1 and Set5 (p = 0.001) and in Set5 between the methods (p = 0.047). For power, there was a difference between Set1 and 5 in TRAD (p = 0.016) and VRT (p = 0.002). Conclusion: We conclude that training with currents (VRT) promoted greater muscle fatigue when compared to traditional training.